2019
DOI: 10.5423/ppj.oa.04.2019.0124
|View full text |Cite
|
Sign up to set email alerts
|

Stress Tolerance and Virulence-Related Roles of Lipopolysaccharide in Burkholderia glumae

Abstract: The lipopolysaccharide (LPS) composed of lipid A, core, and O-antigen is the fundamental constituent of the outer membrane in gram-negative bacteria. This study was conducted to investigate the roles of LPS in Burkholderia glumae, the phytopathogen causing bacterial panicle blight and seedling rot in rice. To study the roles of the core oligosaccharide (OS) and the Oantigen region, mutant strains targeting the waaC and the wbiFGHI genes were generated. The LPS profile was greatly affected by disruption of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 56 publications
4
10
0
2
Order By: Relevance
“…The phage-resistant P. parmentieri mutants, while having altered polysaccharide synthesis, also expressed various phenotypes that are likely not directly related to phage-resistance but apparently contribute to their environmental fitness. Other studies of mutants with defects in LPS have revealed their role in resistance to different stresses [ 67 , 68 ]. Likewise, mutations resulting in alternations of the LPS structure were found to be associated with the altered ability to form biofilm and/or to survive under various abiotic stresses [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…The phage-resistant P. parmentieri mutants, while having altered polysaccharide synthesis, also expressed various phenotypes that are likely not directly related to phage-resistance but apparently contribute to their environmental fitness. Other studies of mutants with defects in LPS have revealed their role in resistance to different stresses [ 67 , 68 ]. Likewise, mutations resulting in alternations of the LPS structure were found to be associated with the altered ability to form biofilm and/or to survive under various abiotic stresses [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hot CYMG-0.5% agar and hot CYMG-0.25% agar (15 mL) was poured into Petri dishes for swarming assay and swimming assay, respectively [ 28 , 32 ]. The plates were dried.…”
Section: Methodsmentioning
confidence: 99%
“…For example, mutations in LPS biosynthesis-related genes of Salmonella enterica resulted in the loss of its virulence ( Kong et al, 2011 ). Similarly, mutation of genes involved in the synthesis of the core oligosaccharide (OS) of LPS, resulted in clear reduction in the virulence of Burkholderia glumae that causes bacterial panicle blight and seedling rot in rice ( Lee et al, 2019 ). Since PMI is involved in the production of intermediates used for the synthesis of the OS of LPS, our data coincide with these previous data.…”
Section: Discussionmentioning
confidence: 99%